1996
DOI: 10.1016/s0014-5793(96)01219-7
|View full text |Cite
|
Sign up to set email alerts
|

Core promoter elements are essential as selective determinants for function of the yeast transcription factor GAL11

Abstract: The GALll gene product, which copurifies with RNA polymerase II holoenzyme, is necessary for full expression of many, but not all, genes in yeast. Here we shows that the GALll dependence of a gene for expression is determined by the core promoter structure. In the GAL80 gene, a gall1 null mutation caused reduction of TATA-dependent transcription, but exerted no effect on initiator-mediated transcription. GALll stimulated TATA-dependent transcription, but did not affect the TATAindependent transcription in HIS4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…We previously suggested that GAL11 is required for maximal transcription of various genes containing the TATA box (27). Here we have shown that transcription from TATA-containing 5), TFIIE-⌬C (lanes 2 and 3), and Gal11 (lanes 3 and 5) were added to the indicated reaction mixtures.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…We previously suggested that GAL11 is required for maximal transcription of various genes containing the TATA box (27). Here we have shown that transcription from TATA-containing 5), TFIIE-⌬C (lanes 2 and 3), and Gal11 (lanes 3 and 5) were added to the indicated reaction mixtures.…”
Section: Discussionmentioning
confidence: 77%
“…Rich glucose (YPD), enriched synthetic, synthetic complete, and 5-fluoroorotic acid-containing media were prepared as described (24,27,28). Galactose utilization of cells was assayed using EBGal medium (18).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, the mediator complex, a component of the RNA-polymerase II holoenzyme, which is indispensable for regulated gene expression, might serve as coactivator (40,41). For instance, Gal11p, a component of the mediator, is essential for regulated expression of GAL80, but not required for initiator-dependent constitutive transcription of this gene (42). The mechanism that distinguishes between TATA-containing and TATA-less promoters remains to be elucidated.…”
Section: Inversion Of the Intergenic Region Between Gcy1 And Rio1-mentioning
confidence: 99%